2020
DOI: 10.1021/acs.energyfuels.0c02041
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Syngas-Fueled Chemical Looping Combustion System

Abstract: The syngas-fueled chemical looping combustion (CLC) system is numerically investigated by means of the two-fluid model. The influence of heterogeneous structures on the performance of the CLC system is taken into account by using a structurebased mesoscale drag model, while the effect of water−gas-shift (WGS) reaction is further considered in the current simulation. When the effect of the WGS reaction is considered in the reactive kinetic model, the product gas yields can be accurately predicted at the reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Shuai et al [22] simulate the hydrodynamics and also chemical reaction kinetics of a fuel reactor using k-FIX, which is a precursor of MFIX software, choosing the total variation diminishing method (TVD) scheme to solve the equations. The work of [23] assumes a particularly interesting meaning, if compare with the work presented in this paper, because it shows which could be the future developments, after the simulation and optimization of the batch fuel reactor. Continuous process in fact will have to be studied.…”
Section: Advancement On Cfd Models On Chemical Looping Combustionmentioning
confidence: 85%
“…Shuai et al [22] simulate the hydrodynamics and also chemical reaction kinetics of a fuel reactor using k-FIX, which is a precursor of MFIX software, choosing the total variation diminishing method (TVD) scheme to solve the equations. The work of [23] assumes a particularly interesting meaning, if compare with the work presented in this paper, because it shows which could be the future developments, after the simulation and optimization of the batch fuel reactor. Continuous process in fact will have to be studied.…”
Section: Advancement On Cfd Models On Chemical Looping Combustionmentioning
confidence: 85%
“…used CFD simulations to analyze how various reactor sizes impact the circulation rate of the oxygen carrier and identified the optimal reactor size, significantly enhancing the reaction performance of the oxygen carrier. With regard to the optimization of process flow, reaction conditions significantly influence the energy consumption and gas production of the system. Aspen Plus is a chemical process simulation software that can simulate the gas yield under different conditions. Zeng et al employed Aspen Plus to simulate the coal chemical looping hydrogen production process and explored the impact of various operational parameters on hydrogen output. Their findings indicated that hydrogen production was 30% greater than that of conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…The two-fluid method (TFM) is a typical Euler–Euler approach, in which both gas and solid phases are considered continuous phases. Consequently, this approach greatly reduces computational costs and can simulate CLC from the laboratory to the pilot scale. However, this approach has major limitations, such as the closure problem and the inability to obtain particle-scale information, , and it is consequently unsuitable for investigating the actual pathways of particles and particle size polydispersity. In contrast, the Euler–Lagrange approach treats only the fluid phase as a continuum but considers the particles as discrete entities.…”
Section: Introductionmentioning
confidence: 99%